VDC_100102372010.0X000001. Issue 1 (January 2018) - Allen, Casey J.; Subhawong, Ty K.; Hanna, Mena M.; Chelala, Lydia; Bullock, M. Ross; Schulman, Carl I.; Proctor, Kenneth G.
Arginine vasopressin (AVP) is often used as an alternative pressor to catecholamines (CATs). However, unlike CATs, AVP is a powerful antidiuretic that could promote edema. We tested the hypothesis that AVP promoted cerebral edema and/or increased requirements for osmotherapy, relative to those who received CATs, for cerebral perfusion pressure (CPP) management after traumatic brain injury (TBI). This is a retrospective review of 286 consecutive TBI patients with intracranial pressure monitoring at a single institution from September 2008 to January 2015. Cerebral edema was quantitated using CT attenuation in prespecified areas of gray and white matter. Results: To maintain CPP >60 mm Hg, 205 patients required no vasopressors, 41 received a single CAT, 12 received AVP, and 28 required both. Those who required no pressors were generally less injured; required less hyperosmolar therapy and less total fluid; and had lower plasma Na, lower intracranial pressure, less edema, and lower mortality (all P < 0.05). Edema; daily mean, minimum, and maximum Na levels; and mortality were similar with AVP versus CATs, but the daily requirement of mannitol and 3 per cent NaCl were reduced by 45 and 35 per cent (both P < 0.05). In patients with TBI who required CPP therapy, AVP reduced the requirements for hyperosmolar therapy and did not delay resolution or increase cerebral edema compared with CATs.